Meta-analysis of the effect of vitamin D on depression - Wang, Lu; Su, Siyuan; Liu, Yongsheng (Frontiers in Psychiatry, 2025)
ObjectiveTo investigate the effect of vitamin D supplementation on depressive symptoms by conducting a meta-analysis of randomized controlled trials.MethodsWe systematically searched PubMed, EMBASE, the Cochrane Library, CNKI, VIP, Wanfang, and additional databases for relevant literature published between January 1, 2000, and October 31, 2024. Two independent reviewers screened titles, abstracts, and full texts, extracted data, and assessed study quality. RevMan 5.3 software was employed to calculate pooled effect sizes and assess heterogeneity.ResultsTwenty trials met our inclusion criteria. Meta-analysis using a random-effects model demonstrated that vitamin D supplementation significantly reduced depressive symptom scores compared to controls (standardized mean difference [SMD] = –0.36; 95% confidence interval [CI], –0.52 to –0.20; P < 0.00001).ConclusionOur findings indicate that vitamin D supplementation is associated with a moderate but statistically significant improvement in depressive symptoms. These results support the potential role of vitamin D as an adjunctive treatment for depression, particularly in individuals with baseline deficiency.